Una visión de la libertad de comunicación desde la perspectiva de las diferencias entre la libertad de expresión, en sentido estricto, y la libertad de información - García Guerrero, José Luis (Teoría y Realidad Constitucional, 2007)
The present Project contains a complete synthesis of the constitutional Spanish jurisprudence. The author considers that the right to freedom and the political rights are grouped around three or four genres. It identifies, between those, the freedom of communication that the constitutional assembly and the constitutional jurisprudence have extended to all sorts of activities. After this assumption, the project is focused on giving a view of the freedom of communication from the point of view of the differences between the freedom of information and the freedom of speech in a strict way. After defending a legal nature which protects all kinds of communications and which can be exercised by all sorts of chaps; it is rejected that the institutional offshoot explains the really different limitations that several messages introduce, wide restrictions regarding commercial speech or pornography and dropped ones regarding politics. The argument which is proposed for its justification is based on the different systematic connections that are originated between the constitutional rules by the different matter and the purpose pursued by the messages, and, when this yardstick is insufficient, it is complemented with the concept of relevance or public interest, the one which is pretended to be refined. The exercise of that freedom by journalists and maximizing the professional diligence reinforce the freedom of communication when it has to be pondered with other rights or constitutional goods. In Spain, the affair Terminello versus Chicago is considered as a worth yardstick to solve conflicts with the public order.